Case Report: Esophageal Bronchus in a Neonate, With Image, Histological, and Molecular Analysis - Trisno, Stephen L.; Higano, Nara S.; Kechele, Dan; Nasr, Talia; Chung, Wendy; Zorn, Aaron M.; Woods, Jason C.; Wells, James M.; Kingma, Paul S. (Frontiers in Pediatrics, 2021)
In this case report, we describe the clinical course of a neonate who presented initially with respiratory distress and later with choking during feeding. He was subsequently found to have an esophageal bronchus to the right upper lung lobe, a rare communicating bronchopulmonary foregut malformation. Histological and molecular analysis of the fistula and distal tissues revealed that the proximal epithelium from the esophageal bronchus has characteristics of both esophageal and respiratory epithelia. Using whole exome sequencing of the patient’s and parent’s DNA, we identified gene variants that are predicted to impact protein function and thus could potentially contribute to the phenotype. These will be the subject of future functional analysis.